Building financial empowerment for survivors of domestic violence : a path to hope and freedom - Postmus, Judy L.; Stylianou, Amanda M. (Violence against women and children (New Brunswick, N.J.), 2023)
"Each year, millions of women throughout the world experience violence and abuse at the hands of their intimate partner. Abusers coercively control them by using a variety of tactics ranging from physical or sexual violence to emotional or psychological abuse. An additional tactic often used includes financial abuse in which the abuser controls the money in the family, exploits the victim's financial standing, and interrupts her efforts to be self-sufficient. The impact of financial abuse can leave women financially trapped in the relationship with limited financial management skills, knowledge, or self-confidence. Indeed, survivors often mention financial barriers as a top reason for keeping them trapped by the abuser in the relationship. The work of financial empowerment is critical not only to ensure the long-term safety of survivors but also to assist survivors in gaining long-term economic stability. Curiously, little of the research on domestic violence has sought to either fully understand the impact of financial abuse or to determine which intervention strategies are most effective toward the financial empowerment of survivors. Building Financial Empowerment for Survivors of Domestic Violence aims to address this critical knowledge gap by providing those who work with survivors of domestic violence with practical knowledge on how to empower the financial well-being and stability of survivors. Specifically, every practitioner, human service provider, criminal justice practitioner, financial manager, and corporate supervisor should be screening the women they encounter for economic abuse, and when such abuse is found, then work with the women toward developing financial safety plans, and referring survivors to financial empowerment programs to assist survivors to become free from abuse."--